Upaya Gugatan Perlawanan Debitur Untuk Membatalkan Penjualan Lelang Objek Hak Tanggungan - Grafita Aji Parama Bhakti; Zakki Adhiliyati, S.H., M.H., LL.M (Sebelas Maret University, 2017)
This study aims to determine the suitability of the consideration of judges with law No. 4 of 1996 About security rights in decisions to attempt resistance lawsuit to cancel the auction sale of the debtor object security rights. The method used in this paper is a normative prescriptive and applied. The approach used is a case approach. Sources of legal materials used are primary and secondary legal materials, with materials analysis techniques that are legal syllogism deductive method. Case originated from PT. BANK MEGA Tbk Cq. BANK MEGA Branch of Magelang as creditor who has tendered against the collateral of the debtor named Ahmad Zuhri of 1 (one) parcels of land and buildings, following everything that stands on it. But the tender process was delayed due to a lawsuit opposition from the debtor, whereas a settlement through legal institutions in practice would be detrimental to the debtor because it takes time, cost and effort is not small, as well as the interest to be paid to the creditors will continue to accumulate during the judicial process ongoing. Creditors will also be harmed because they do not immediately get the repayment of debt as a result of the execution process convoluted in court. Based on research, it can be concluded the judges stated that the execution of the security rights is legitimate and in accordance with article 20 of Law No. 4 of 1996 concerning security rights, and rejected the lawsuit filed by the debtor resistance. Keywords: Creditors, Debtors, Security rights